Association between maternal exposure to elevated ambient temperatures and adverse birth outcomes, and potential effect modification of sociodemographic and economic factors: A study in Queensland, Australia - Dalugoda, Yohani; Linh Tran, Nu Quy; Vilcins, Dwan; Darssan, Darsy; Pizzino, Stacey; Phung, Dung (Environmental research, 2025)
The association between high ambient temperatures and adverse birth outcomes (ABOs) is gaining global attention; however, evidence from Queensland, Australia, is limited and inconsistent. This study examined the associations between average maximum temperatures (AMTs) and ABOs, including preterm birth (PTB), low birth weight (LBW), stillbirth, congenital anomalies, and neonatal deaths, across 82 statistical areas level 3 (SA3) in Queensland. The study further investigates whether sociodemographic and economic factors modify these relationships. Using multivariable binary logistic regression and random-effects meta-analysis, the study estimated SA3-specific and pooled effects. Meta-regression explored the influence of sociodemographic and economic factors. Greater AMT-ABO risk observed in remote and regional SA3s than urban SA3s. A 1°C increase in AMT was associated with higher odds of PTB (0.6% [95%CI: 0.2–0.9]) during the 0-8 weeks of gestation, LBW during weeks 13 to 26 (0.7% [95% CI, 0.2–1.1]) and final week (0.4% [95% CI, 0.0–0.7]). AMT was also linked with congenital anomalies in the last four weeks (0.5% [95% CI, 0.2–0.7]) and the final week (0.6% [95% CI, 0.2–0.9]), and neonatal deaths from 27 weeks until birth (3.4% [95% CI, 0.0–6.8]). No significant association was found for stillbirth. The association between AMT-congenital anomalies was stronger in lower income communities, while the association with stillbirth was more pronounced in communities with higher Indigenous population. No other sociodemographic or economic factors had significant modifying effects. Our findings highlight the urgent need to implement targeted heat-health interventions to protect Queensland mothers and newborns from high temperatures. •High temperatures increase risk of adverse birth outcomes in Queensland•Remote/regional areas face higher heat-adverse birth outcomes risk than Urban areas•Each 1°C rise increases risk of PTB, LBW, congenital anomalies, and neonatal death•Low-income and Indigenous groups face highest risk of heat-related birth outcomes